Sleep quality, social rhythms, and depression among people living with HIV: a path analysis based on social zeitgeber theory - Meng, Jingjing; Xiao, Xueling; Wang, Wenru; Jiang, Ying; Jin, Yanfei; Wang, Honghong (Frontiers in Psychiatry, 2023)
Background: People living with HIV frequently report sleep disturbances. The social zeitgeber theory, which proposes that stressful life events can interfere with sleep and even depression by destabilizing daily routines, provides new insights into identifying predictors of sleep disturbances and improving sleep in people living with HIV. Objective: To explain the pathways affecting sleep quality in people living with HIV based on social zeitgeber theory. Methods: A cross-sectional study was conducted to assess sleep quality, social rhythms, depression, social support, and coping styles from December 2020 to February 2021. The hypothetical model was tested and respecified by performing path analysis and a bias-corrected bootstrapping method using IBM AMOS 24 software. The report of this study followed the STROBE checklist. Results: A total of 737 people living with HIV participated in the study. The final model presented a good fit (goodness of fit = 0.999, adjusted goodness of fit index = 0.984, normed fit index = 0.996, comparative fit index = 0.998, Tucker–Lewis index = 0.988, root mean square error of approximation = 0.030, chi-squared/degree of freedom = 1.646), explaining 32.3% of the variance in sleep quality among people living with HIV. Lower social rhythm stability was directly associated with poorer sleep quality, and depression mediated the relationship between social rhythms and sleep quality. Social support and coping styles affected sleep quality through social rhythms and depression. Limitation: The cross-sectional study design precludes making assumptions about causality among factors. Conclusion: This study validates and extends the applicability of the social zeitgeber theory in the HIV context. Social rhythms have direct and indirect effects on sleep. Social rhythms, sleep, and depression is not simply linked in a cascading sequence but is theoretically linked in a complex way. More studies are needed to explore the predictors of social rhythms, and interventions for stabilizing social rhythms have the potential to alleviate sleep disturbances and depression in people living with HIV.